Up in smoke: the passage of medical marijuana legislation and enactment of dispensary moratoriums in Massachusetts - Socia, Kelly M. (Crime & delinquency, 2017)
In November 2012, Massachusetts’ voters passed a medical marijuana law that was soon followed by municipal moratoriums prohibiting marijuana dispensaries. This study uses structural equation modeling (SEM) to examine (a) whether municipal characteristics predict voting outcomes for medical marijuana, (b) whether these same characteristics predict moratorium enactment, and (c) whether voting outcomes mediate the relationships between municipal characteristics and moratorium enactment. Results indicate that municipal characteristics predict voter support and indifference for medical marijuana, and this support and indifferences in turn predicts moratorium passage. However, most municipal characteristics only indirectly affect moratorium passage via voting activity. This suggests moratorium enactment may be an extension of municipal voting activity, in turn reflecting the characteristics of a municipality’s population. Policy implications are discussed.